Difficulty and Mastery of Physics Concepts for Middle School Students in Density Material - Nukhba, Rania; Wulandari, Ika Pratiwi; Ulum, Fatchul; Parno, Parno (Kasuari: Physics Education Journal (KPEJ), 2024)
The purpose of this research is exploring the student’s density conception as early as possible so that when heading to essential topics that involve density in physics (like statics and dynamics fluid), students can easily understand these essential topics. In general, students' concept understanding of density is already relatively high with 63,5%. There are differences between the conceptual understanding of male and female students, which the conceptual understanding of density in female students was better than male students. The notable difference between them is the understanding of the concepts relating mass, volume, and density. Some students also shown that they had not been able to understand the basic conception of the density and properties of matter. For further research, it is better to provide a short interview session and give students the opportunity to describe mental models of the properties of substances that students have understood.